2022
DOI: 10.1021/acs.inorgchem.2c01465
|View full text |Cite
|
Sign up to set email alerts
|

Emission Enhancement and Energy Transfers in YV0.5P0.5O4 Nanoparticles Codoped with Eu3+ and Bi3+ Ions

Abstract: In this study, solid-state solutions of yttrium orthovanadate-phosphate with varying concentrations of codopants (Eu 3+ , Bi 3+ ) have been obtained via coprecipitation. An ionic radii mismatch between V 5+ and P 5+ substituents is manifested in broad XRD lines. The sharpening of the XRD lines is observed with increasing bismuth ions concentration in the Eu 3+ codoped YV 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Among various vanadate systems, orthovanadates (M II 3 V 2 O 8 ) exhibit promising luminescence features that arise because of the previously mentioned LMCT luminescence. [23][24][25] Particularly, Zn 3 V 2 O 8 is studied as a significant self-activated yellow light emitter with excitation under n-UV light, good quantum efficiency (QE) and high thermal stability. 26 Qian et al 27 and Li et al 28 previously reported a solid-state synthesized Zn 3 V 2 O 8 phosphor that emits broad yellow emission due to n-UV excitations with QEs B43.6% and B51%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among various vanadate systems, orthovanadates (M II 3 V 2 O 8 ) exhibit promising luminescence features that arise because of the previously mentioned LMCT luminescence. [23][24][25] Particularly, Zn 3 V 2 O 8 is studied as a significant self-activated yellow light emitter with excitation under n-UV light, good quantum efficiency (QE) and high thermal stability. 26 Qian et al 27 and Li et al 28 previously reported a solid-state synthesized Zn 3 V 2 O 8 phosphor that emits broad yellow emission due to n-UV excitations with QEs B43.6% and B51%, respectively.…”
Section: Introductionmentioning
confidence: 99%